Ethical Enjoyment With Other Faces In Papua Student's Life In Malang City - Imanuel Tenau (International Journal of Social Service and Research, 2022)
The gate of Plato's Academia school of philosophy is emblazoned with the words know yourself. Know yourself, this is the first door to enter the gate of philosophizing activity. Levinas gave the gate a face that presented himself to the others. Self is the first human awareness to relate to others (the other). The other is a picture of the esse in its totality to create an encounter between faces. The face displays its esse facticity which places me and the others in its temporality. The encounter between two faces describes human life which is often discussed by everyone so far. The discussion that always arises is the difficulty of accepting the existing differences. Differences in culture, ethnicity, character, religion lead people to not respect or accept one another. The personal dimension in humans expresses the quality in oneself that is unique so that it distinguishes it from others. Here man is able to determine himself and all his actions. Likewise, the social dimension makes humans unable to live alone. This condition will make humans act specifically as humans. The presence of others for humans also leads humans to their wholeness. The results of this study intend to present face-to-face encounters. This point has been pondered, written about and discussed by quite a number of philosophers. It is not my intention, however, to examine everything that many or all philosophers have to say on the subject. I just want to limit it to what one philosopher said, namely Emanuel Levinas. Nor will I deny that there was an attempt to introduce him and his way of thinking to a somewhat restricted environment. However, on this occasion I would like to introduce this character and his main ideas to the indigenous Papuan environment as Melanesian faces with non-Papuan faces as Malay faces.